2017
DOI: 10.1080/15592294.2016.1278095
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification in chromatin machinery and its deregulation in pediatric brain tumors: Insight into epigenetic therapies

Abstract: Malignancies are characterized by the reprogramming of epigenetic patterns. This reprogramming includes gains or losses in DNA methylation and disruption of normal patterns of covalent histone modifications, which are associated with changes in chromatin remodeling processes. This review will focus on the mechanisms underlying this reprogramming and, specifically, on the role of histone modification in chromatin machinery and the modifications in epigenetic processes occurring in brain cancer, with a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 145 publications
(221 reference statements)
1
38
1
Order By: Relevance
“…We have previously shown that inhibition of the H3K27 demethylase JMJD3 by GSK-J4 acts to restore K27 methylation in DIPG cells (10). Increased H3K27 methylation promotes heterochromatin, which is transcriptionally silent and decreases gene expression (27). In our current study, GSK-J4-mediated H3K27 methylation significantly decreases DNA accessibility at both promoter and distal binding sites ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We have previously shown that inhibition of the H3K27 demethylase JMJD3 by GSK-J4 acts to restore K27 methylation in DIPG cells (10). Increased H3K27 methylation promotes heterochromatin, which is transcriptionally silent and decreases gene expression (27). In our current study, GSK-J4-mediated H3K27 methylation significantly decreases DNA accessibility at both promoter and distal binding sites ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 58%
“…The mutant protein sequesters and functionally inactivates EZH2, a catalytic subunit of the K27 histone methyltransferase, polycomb repressive complex 2 (PRC2), leading to a dramatic reduction in global methylation at K27 residues in the K27M DIPG (7,8). This reduction in H3K27 methylation leads to opening of the chromatin providing access for active transcription (26,27). We have previously shown that inhibition of the H3K27 demethylase JMJD3 by GSK-J4 acts to restore K27 methylation in DIPG cells (10).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying REST-dependent upregulation of GREM-1 is a subject of ongoing investigation. REST is associated with a number of chromatin remodeling enzymes, whose activity can be inhibited by drugs that are currently in use in the clinic or are being investigated in pre-clinical studies [ 5 , 92 94 ]. These agents may have applications in the treatment of REST-expressing DIPGs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several members from the chromatin-remodeling families are known to be mutated in human malignancies, raising the possibility that abnormal activities of chromatin remodeling may be the driving force for tumor initiation and progression [31,75]. In brain tumors, genetic defects of the enzymes which are involved in the chromatin remodeling are reported to be the hallmark aberration in some tumor types, notably as driver mutations in histone H3.3 and chromatin remodeling genes in pediatric GBM [58,70].…”
Section: Chromatin Remodelersmentioning
confidence: 99%